The Effect of Leadershi and Personal Factor on Employee’s Performance with a Motivation as an Intervening Variable: The Case of PT. Pupuk Sriwidjaja Palembang - Fatrin, Dian Kartika; Moelyati, Trisniarty Adjeng; Fatimah, Fatimah (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This research aims to determine the influence of leadership and personal factors on employee performance at PT. Pupuk Sriwijaya Palembang, with motivation as an intervening variable. This is an associative study. The variables used in this research include leadership, personal factors, motivation, and employee performance. The sample consists of 120 PT employees. Pupuk Sriwidjaya Palembang, selected using Cluster Sampling. The primary data used in this research was collected through a questionnaire. Data analysis was conducted using Structural Equation Modeling (SEM) with the Lisrel application. Research Findings: 1. Leadership positively and significantly affects work motivation. 2. Personal factors have a positive and significant effect on work motivation. 3. Leadership has a positive and significant effect on employee performance. 4. Personal factors negatively but not significantly affect employee performance. 5. Motivation has a positive and significant effect on employee performance. 6. Motivation strengthens the influence of leadership on employee performance. 7. Motivation also strengthens the influence of personal factors on employee performance at PT. Pupuk Sriwidjaya Palembang